Worksheets as a scaffolding tool to build up grammatical competence among students of tenth year “a” of basic education, afternoon session at unidad educativa fiscomisional mercedes de jesús molina in loja city during the 2020 – 2021 school year. - Vivanco Carrión, Carlos Xavier (2021)
The present research work was aimed to build up grammatical competence through worksheets as a scaffolding tool among tenth grade "A" students. The methods used in this research to collect, describe, process, interpret and analyze the data were the scientific, descriptive, statistical, and analytical-synthetic. Tests and questionnaires were applied to 21 students at the beginning and at the end of the intervention plan. Observation sheets were also used to analyze and record the students' progress in grammar competence, and field notes were used to record the students' attitudes in relation to the worksheets. The results showed that the students satisfactorily developed their skills in grammatical competence, such as writing short sentences, identifying the parts of a sentence and the rules of each grammatical structure. Overall, the application of the worksheets as a scaffolding tool motivated students to actively participate in class building their own knowledge and consequently become independent learners.